Endoscopic treatment of anastomotic leakage after esophagectomy or gastrectomy for carcinoma with self-expanding removable stents - Alldinger, Ingo; Schmitt, Marcus M.; Dreesbach, Jens; Knoefel, Wolfram T. (Hepato-gastroenterology journal, 2014)
BACKGROUND/AIMS: Anastomotic leakage is a feared complication after gastrectomy and esophagectomy. We report our experience in the treatment with endoscopic stent placement. - METHODOLOGY: Seventeen patients with anastomotic leakage after resection of a malignant tumor of the stomach or the distal esophagus have been long-term followed-up. - RESULTS: In 10 patients the implanted stent did successfully close the leakage in the first attempt. In 3 out of 7 patients with unsuccessfully sealed leakage a stent-in-stent-manoeuvre did successfully seal the leakage. We had no major complications upon implantation of the stents. We did have no recurrence of a once sealed leakage. - CONCLUSIONS: Endoscopic stent placement is a safe procedure in the treatment of anastomotic leakage after gastrectomy and esophagectomy. It should be performed in any clinically relevant leakage if possible. In cases where stent placement is not successful at first, correction of position, stent replacement or a stent-in-stent manoeuvre can be performed, with promising results.